DETERMINING THE COST OF HOTEL ROOMS USING THE ACTIVITY BASED COSTING METHOD AT GUARDIAN FAMILY HOTEL SORONG - Maria Jolanda Horet Kung; JEMMY POANDY; Dina Palijama (LPPM Politeknik Saint Paul Sorong, 2021)
Methods of Activity Based Costing System is a method to apply the concept of cost accounting to determine the price more accurately. This paper aims to determine differences in calculating the cost of a hotel room using simple method and using Activity Based Costing System. Guardian Family Hotel calculate the cost of the hotel rooms using simple method. Therefore, the author calculated the cost of the room by using Activity Based Costing System that gives a more accurate price